Mucinous adenocarcinoma of the prostate with extremely low prostate-specific antigen levels, recurrent disease: a case report - Yu, Xu; Yuan, Jie; Wang, Zhiming; Wang, Niannian; He, Xiangfei; Liu, Jie (Frontiers in Oncology, 2025)
Mucinous adenocarcinoma (MC) is a very rare type of prostate cancer, accounting for less than 1% of prostate adenocarcinomas, and its etiology is still unclear. Its clinical symptoms are similar to those of prostate hyperplasia and follicular carcinoma of the prostate, which are often misdiagnosed, and a definite diagnosis depends on pathological diagnosis, and the secretion of a large amount of mucus is its pathological characteristic. Surgery and endocrine therapy are the main treatment modalities, followed by radiation therapy and comprehensive therapy. Since this disease is rarely reported, in order to improve the understanding and diagnosis of clinically rare MC, we report a case of primary recurrent mucinous adenocarcinoma of the prostate and analyze its clinical features, pathological diagnosis, treatment and prognosis in the light of the literature.